MANAJEMEN PROGRAM PENDIDIKAN BERBASIS PRODUKSI DI AKADEMI TEKNIK SOROAKO - Wardoyo, Setyo (Pascasarjana Universitas Negeri Makassar, 2015)
The study aimed at discovering (1) the description of the planning of Production-based Education Program at Engineering Academy in Soroako, (ii) the description of the organization of Production-based Education Program at Engineering Academy in Soroako, (iii) the implementation of Production-based Education Program at Engineering Academy in Soroako, and (iv) the monitoring technique of Production-based Education Program at Engineering Academy in Soroako. The study employs descriptive-qualitative approach with a case study. Data were collected through interview, observation, and documentation which analyzed by employing Miles and Huberman model.The results of the study revealed that (i) the planning of the implementation of production-based education program was conducted well such as cunducting the bench marking with other higher institutions, forming the team consisted of PDI, Kaprodi, and Sekprodi, the management conducted orientation to the instructors and lecturers as well as preparing the SK of instructor but it did not separate which one is production-based education and non production-based education, preparing learning material such as raw material, machine/equipment, blue print and APD were prepared well and preparing learning package administration well such as GBPP, SAP, AI, and source contract, (ii) the organization in relation to the curriculum which based on the Production-based Education Program for level 1 student was still in introduction, whereas level 2 and level 3 involved more on the Production-based Education Program, especially the level 3 students. The human resources of lecturers referred to maps of lecturer competence which updated by PSDM unit whereas, the budget used was fully depend on the Soroako Edducation Foundation (YPS) which was PT. Vale Indonesia, Tbk., (iii) the implementation of mobilization of Producttion-based Education Program was led to the responsibility of the lecturers, instructors, and structural officials based on the role and accountability standard book in each of work unit, thus, the role and accountability of the lecturers, instructors, and structural officials were tangible in engineering Academy in Soroako, (iv) the monitoring was conducted to ensure that the curriculum had linked with the industry, controlled whether the curriculum had been conducted based on the plan, so the team had coordination with the Head of Study Program. In terms of the result of practice performance, the measurement of the performance was conducted at the end of the program. If the program completed, it meant that it was implemented. The custemer satisfaction was reported by Students Unit and Production Unit to the Director in coordination meeting of Directors as well as ISO Quality management Review meetng on the achievement of KPI.